Electrode material and method for producing the same
A phosphate-based water-resistant layer on lithium vanadium phosphate addresses the issue of structural changes due to moisture, ensuring stable electrode performance and vanadium retention.
Patent Information
- Application Number
- JP2020061830
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-31
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-03-31
AI Technical Summary
The crystal structure of lithium vanadium phosphate is susceptible to changes due to moisture in the atmosphere, leading to deterioration in the performance characteristics of electrodes.
A water-resistant layer with a phosphate-based compound, such as aluminum phosphate or titanium phosphate, is applied to lithium vanadium phosphate to prevent structural changes, enhancing its durability against moisture.
The application of a phosphate-based water-resistant layer effectively suppresses structural changes in lithium vanadium phosphate, maintaining electrode performance and preventing vanadium elution, while maintaining charge-discharge characteristics.
Smart Images

Figure 0007609562000003 
Figure 0007609562000004 
Figure 0007609562000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode material used in electricity storage devices such as secondary batteries and electrochemical capacitors, and a method for producing the electrode material. [Background technology]
[0002] As electrodes for power storage devices such as secondary batteries and electrochemical capacitors, a positive electrode in which a positive electrode material containing lithium ions and a conductive assistant are fixed to the surface of a metal foil, and a negative electrode in which a negative electrode material capable of inserting and removing lithium ions and a conductive assistant are fixed to the surface of a metal foil are used. In recent years, lithium vanadium phosphate (Li3V2(PO4)3) having a Na Super Ionic Conductor (Na Super Ionic Conductor) structure has been attracting attention as an electrode material.
[0003] Lithium vanadium phosphate is Li / Li + It operates at 3.8V to 4.8V against the reference. It can also exhibit a large capacity of up to 197mAh / g depending on each potential plateau. Lithium vanadium phosphate has a crystal structure that allows lithium to diffuse three-dimensionally, making it possible to charge and discharge at high speeds. Lithium vanadium phosphate with P-O bonds has high thermal stability and is excellent in safety. For these reasons, the use of lithium vanadium phosphate as an electrode material is being promoted. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-52970 A Summary of the Invention [Problem to be solved by the invention]
[0005] As a result of the research conducted by the inventors of the present invention on lithium vanadium phosphate, it was pointed out that the crystal structure of lithium vanadium phosphate may change due to moisture in the air, and it was considered that the change in lithium vanadium phosphate due to moisture may cause deterioration in the performance characteristics of electrodes manufactured using lithium vanadium phosphate.
[0006] The present invention has been proposed to solve the above problems, and has an object to provide an electrode material capable of suppressing changes in crystal structure due to moisture, and a method for producing the electrode material. [Means for solving the problem]
[0007] For example, when lithium vanadium phosphate is left in a high humidity environment with a humidity of 80% or more, the XRD spectrum of the lithium vanadium phosphate changes before and after being left there, and it was presumed that the moisture in the air causes a change in the crystal structure of the lithium vanadium phosphate. Therefore, the inventors conducted extensive research to improve the durability of lithium vanadium phosphate against moisture, and discovered that the change in the crystal structure of lithium vanadium phosphate can be suppressed by providing a specific water-resistant layer on lithium vanadium phosphate.
[0008] In order to achieve the above object, the electrode material according to the present invention comprises lithium vanadium phosphate bonded to a conductive carbon material, the lithium vanadium phosphate having a water-resistant layer. The water-resistant layer has a crystal structure of a phosphate-based compound, and the water-resistant layer having a crystal structure of the phosphate-based compound is an aluminum phosphate compound, a titanium phosphate compound, or α M β (PO 4 ) γ X is any one of Li, Na, K, and Ca, and M is any one of Al, Mn, Co, Fe, Mg, Ni, Ti, Zn, Cr, Ni, Cu, Zr, and Nb, and the water-resistant layer is a water-resistant layer formed before electrode formation. .
[0009] The aluminum phosphate compound is AlPO 4 It may be.
[0010] The titanium phosphate compound is LiTi 2 (PO 4 ) 3 It may be.
[0012] The water-resistant layer may be formed so that its content is 5 to 25 wt % relative to lithium vanadium phosphate.
[0013] The present invention comprises a crystallization step of bonding a conductive carbon material with lithium vanadium phosphate, and a coating step of forming a water-resistant layer on the electrode material obtained by the crystallization step. The coating process includes a mixing process in which a material source for a water-resistant layer is mixed in a solution with the electrode material obtained by the crystallization process, and a firing process in which the solution obtained by the mixing process is fired, and the water-resistant layer has a crystal structure of a phosphate-based compound.
[0014] The water-resistant layer having a crystal structure of the phosphate-based compound is an aluminum phosphate compound, a titanium phosphate compound, or α M β (PO 4 ) γ where X is any one of Li, Na, K, or Ca, and M may be any one of Al, Mn, Co, Fe, Mg, Ni, Ti, Zn, Cr, Ni, Cu, Zr, or Nb. Effect of the Invention
[0016] According to the present invention, it is possible to provide an electrode material capable of suppressing changes in crystal structure due to moisture, and a method for manufacturing the electrode material. [Brief description of the drawings]
[0017] [Figure 1] 1 is a flowchart showing a manufacturing procedure of an electrode material. [Diagram 2] 1 is a flowchart showing a manufacturing procedure for forming a water-resistant layer on an electrode material. [Diagram 3] 1 is a graph showing a diffraction pattern by XRD (X-ray powder diffraction) of a reference example of an electrode material. [Figure 4] HRTEM images of electrode materials of the examples and comparative examples, where (a) and (b) are overall images, and (c) and (d) are partially enlarged images. [Diagram 5] HRTEM images of the electrode material of the example, where (a) and (b) are overall images and (c) and (d) are partially enlarged images. [Figure 6] 1 is a graph showing a diffraction pattern by XRD of an electrode material of a comparative example. [Figure 7] 1 is a graph showing a diffraction pattern by XRD of an electrode material of an example. [Figure 8] 1 is a graph showing a diffraction pattern by XRD of an electrode material of an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [composition] The electrode material of this embodiment includes lithium vanadium phosphate and a conductive carbon material. Lithium vanadium phosphate has a Nasicon structure represented by the general formula LixV2(PO4)3. When lithium vanadium phosphate is used as an electrode material for an electricity storage device, 0≦x≦3 and the valence of vanadium ions can be 3 to 5 due to the desorption and insertion of lithium ions accompanying charge and discharge.
[0019] The lithium vanadium phosphate is bonded to the conductive carbon material and is covered with a water-resistant layer. The bonded state means that the lithium vanadium phosphate is in physical contact with the surface of the conductive carbon material, and the lithium vanadium phosphate and the conductive carbon material are also electrically connected to each other, resulting in high conductivity. For example, this includes a state in which the lithium vanadium phosphate is bonded to the surface of the conductive carbon material at the atomic level and shares a structure.
[0020] In addition, it is preferable that the lithium vanadium phosphate is coated with a water-resistant layer having a crystal structure of a phosphate-based compound. The crystal structure of a phosphate-based compound is a system in which a PO4 tetrahedron is introduced into the crystal, and the lithium vanadium phosphate also has the crystal structure of this phosphate-based compound. Therefore, the water-resistant layer having the crystal structure of a phosphate-based compound has a high affinity with the lithium vanadium phosphate.
[0021] Furthermore, the water-resistant layer having a crystal structure of a phosphate-based compound covers the surface of the lithium vanadium phosphate, and more preferably, the contact surface with the lithium vanadium phosphate forms a solid solution with the lithium vanadium phosphate. The solid solution is a state in which the water-resistant layer is dissolved in the crystal structure of the lithium vanadium phosphate, and part of the vanadium element of the lithium vanadium phosphate is replaced by the metal element of the water-resistant layer while maintaining the original crystal structure. In other words, it is presumed that the boundary between the water-resistant layer and the lithium vanadium phosphate is in a state in which two substances having a crystal structure of a phosphate-based compound are mixed together (solid solution state).
[0022] The water-resistant layer having a crystal structure of a phosphate-based compound may be an aluminum phosphate compound or a titanium phosphate compound. Specifically, it may contain AlPO4 or LiTi2(PO4)3. In addition, the water-resistant layer may be X α M β (PO4) γ where X is Li, Na, K, or Ca, and M is Al, Mn, Co, Fe, Mg, Ni, Ti, Zn, Cr, Ni, Cu, Zr, or Nb. The water-resistant layer is preferably coated to be 5 to 25 wt% of the lithium vanadium phosphate contained in the electrode material. If it exceeds 25 wt%, not only does the electrode capacity decrease but the resistance also increases.
[0023] The electrode material as described above can be formed by, first, forming a precursor of lithium vanadium phosphate in a liquid phase reaction such as a complexation reaction, a hydrolysis reaction, an oxidation reaction, a polymerization reaction, a condensation reaction, etc., and then heating and baking the precursor. For example, the electrode material can be obtained by mixing a phosphate source, a conductive carbon material, a lithium source, and a vanadium source using the Pechini method, and then baking the mixture.
[0024] Secondly, the obtained electrode material is mixed with a material source for a water-resistant layer having a crystal structure of a phosphate-based compound and then fired. That is, a water-resistant layer having a crystal structure of a phosphate-based compound is formed on the electrode material obtained by combining lithium vanadium phosphate and a conductive carbon material.
[0025] In the Pechini method, a mixture of material sources is prepared by adding an organic compound having multiple carboxyl groups and an alcohol having multiple hydroxyl groups. The organic compound having multiple carboxyl groups is added to an aqueous solution containing vanadium ions to form a metal complex. The metal complex is polymerized by an ester reaction when an alcohol having multiple hydroxyl groups is added to the metal complex.
[0026] As the conductive carbon material, carbon nanotubes and conductive carbon black having a hollow shell structure (e.g., Ketjen Black (registered trademark)) are suitable, but carbon black such as carbon nanofibers, acetylene black, amorphous carbon, carbon fibers, natural graphite, artificial graphite, activated carbon, mesoporous carbon, nanoporous carbon, graphene, fullerene, or a mixture of two or more of these can also be used.
[0027] The vanadium source and phosphate source may include metal ammonium salts, acetates, sulfates, nitrates, halides, and chelating agents, whether the lithium vanadium phosphate is produced by hydrolysis or by complexation. Specifically, the vanadium source may be NH4VO3. However, it may also be V2O5, V2O3, metallic vanadium, V2O4, vanadium(III) acetylacetonate, or vanadium(IV) oxyacetylacetonate.
[0028] The phosphate source can be H3PO4, but can also be any PO4-containing compound such as NH4H2PO4, (NH4)2HPO4, P2O5, and Li3PO4.
[0029] Lithium sources include CH3COOLi, but may also be LiNO3, Li2CO3, LiOH, LiOH·H2O, LiCl, Li2SO4, and LIC3H5O3.
[0030] An example of an organic compound having multiple carboxyl groups is the tricarboxylic acid citric acid, but it may also be a dicarboxylic acid such as oxalic acid, malonic acid, or succinic acid. An example of an alcohol having multiple hydroxyl groups is ethylene glycol, but it may also be other dihydric alcohols such as propylene glycol, or trihydric alcohols such as glycerin, or polyalcohols such as polyvinyl alcohol.
[0031] The material sources for the water-resistant layer include a metal source and a phosphate source, which are mixed with the electrode material and then re-fired to form a water-resistant layer that covers the electrode material. The phosphate source can be a PO4-containing compound such as H3PO4, NH4H2PO4, (NH4)2HPO4, P2O5, or Li3PO4. When the water-resistant layer contains AlPO4, the metal source can be Al(NO3)3, but it can also be triisopropoxyaluminum, metallic aluminum, alumina, or other inorganic or organic salts of aluminum.
[0032] In addition, when the water-resistant layer contains LiTi2(PO4)3, Ti(O n Bu)4, but titanium oxide, titanium alkoxide, etc. may also be used. When the water-resistant layer contains LiTi2(PO4)3, in addition to the phosphate source and metal source, the material sources include a lithium source and an organic compound having multiple carboxyl groups. Lithium sources include CH3COOLi, LiNO3, Li2CO3, LiOH, LiOH·H2O, LiCl, Li2SO4, and LIC3H5O3. Organic compounds having multiple carboxyl groups include the tricarboxylic acid citric acid, but may also be dicarboxylic acids such as oxalic acid, malonic acid, and succinic acid, or polycarboxylic acids such as polyacrylic acid.
[0033] [Manufacturing method] The method for producing an electrode material according to the present embodiment includes the following steps. (1) A crystallization process that bonds the conductive carbon material with lithium vanadium phosphate (2) A coating process for forming a water-resistant layer on the electrode material obtained by the crystallization process
[0034] (1) Crystallization process The crystallization step is a step of bonding lithium vanadium phosphate to the surface of a conductive carbon material. An example of the crystallization step by the Pechini method will be described below with reference to Figure 1. However, as long as the conductive carbon material and lithium vanadium phosphate are bonded in the crystallization step, the specific method is not limited to the following.
[0035] In other words, the order of mixing the material sources and the number and timing of firing can be appropriately changed. In addition, the liquid phase reaction used to form the lithium vanadium phosphate precursor is not limited to a complex formation reaction, and other reactions such as a hydrolysis reaction, an oxidation reaction, a polymerization reaction, and a condensation reaction can also be used.
[0036] In the crystallization process, first, a phosphoric acid source and a conductive carbon material are added to water to perform the first mechanochemical treatment. Note that a vanadium source may be mixed in place of the phosphoric acid source. The mechanochemical treatment is a treatment in which mechanical energy such as shear stress or centrifugal force is applied using a rotating reaction vessel or the like. The mechanochemical treatment is a process similar to ultra-centrifugal treatment (Ultra-Centrifugal Treatment). It is sufficient to apply shear stress, centrifugal force, or other mechanical energy by using a UC processing method, etc. In short, it is sufficient to obtain a dispersion of a phosphate source or vanadium source and a conductive carbon material by mechanical energy, to attach the phosphate source or vanadium source to the conductive carbon material, and to generate base points of lithium vanadium phosphate on the surface of the conductive carbon material.
[0037] In mechanochemical processing, a solution is subjected to shear stress and centrifugal force in a rotating reactor. The reactor used is preferably a reactor consisting of an outer cylinder and an inner cylinder, with a through hole in the side of the rotatable inner cylinder and a sheathing plate at the opening of the outer cylinder. It is believed that this mechanical energy is converted into chemical energy required for the reaction, the so-called activation energy. This allows the reaction to proceed in a short period of time. A force of 1500 N (kgms s) is required to provide sufficient mechanical energy. -2 It is desirable to generate a centrifugal force of 60,000N (kgms -2 )That's all.
[0038] Secondly, a second mechanochemical treatment is performed to generate a precursor of lithium vanadium phosphate based on the lithium vanadium phosphate generated on the surface of the conductive carbon material. For example, a vanadium source, an organic compound having multiple carboxyl groups, and a lithium source are added to a dispersion of a phosphoric acid source and a conductive carbon material. Furthermore, an alcohol having multiple hydroxyl groups is added, and a second mechanochemical treatment is performed.
[0039] The mechanochemical treatment described above can also serve as a treatment for finely dispersing and highly dispersing the lithium source, vanadium source, phosphate source, and conductive carbon material. By subjecting the lithium source, vanadium source, and phosphate source to mechanochemical treatment, it is possible to promote the production of the lithium vanadium phosphate precursor through a complex formation reaction, a hydrolysis reaction, a polymerization reaction, a condensation reaction, or the like, promote the bonding between the lithium vanadium phosphate precursor and the conductive carbon material, and form the lithium vanadium phosphate precursor into nanoparticles.
[0040] In the above example, the mechanochemical treatment is performed twice, but from the viewpoint of achieving fine particles and high dispersion, the mechanochemical treatment may be performed three or more times by adding the mechanochemical treatment after mixing each material source. Also, the lithium source, vanadium source, phosphate source, conductive carbon material, and other material sources may be mixed at once, and the mixed solution may be subjected to the mechanochemical treatment once.
[0041] Thirdly, the solution is concentrated and dried using an evaporator, vacuum dried at 80-130°C, and then pre-baked in an air atmosphere at 250-300°C for 3-5 hours. This heat treatment in pre-baking removes carbon other than the conductive carbon material. In addition, organic compounds having multiple carboxyl groups, alcohols having multiple hydroxyl groups, and polymers formed by esterification of organic compounds having multiple carboxyl groups and alcohols having multiple hydroxyl groups are removed.
[0042] Furthermore, the mixture is fired in a nitrogen atmosphere at 700 to 900°C for 5 to 120 minutes. During this firing, the vanadium is oxidized without agglomeration, and the crystallization of lithium vanadium phosphate proceeds. This results in an electrode material of a composite powder in which nanoparticles of lithium vanadium phosphate are bonded to the surface of the conductive carbon material. This is the process of the crystallization.
[0043] (2) Coating process In the coating step, a water-resistant layer is formed on the electrode material obtained by the crystallization step. The coating step is performed on the electrode material in which the lithium vanadium phosphate is bonded to the surface of the conductive carbon material through crystallization. An example of the coating step for forming a water-resistant layer is described below with reference to FIG. 2.
[0044] First, the source material for the water-resistant layer and the electrode material obtained in the crystallization process are added to a liquid in which the source material for the water-resistant layer is soluble, and a mechanochemical treatment is performed. By this mechanochemical treatment, the source material for the water-resistant layer and the electrode material are finely divided and dispersed in the solution.
[0045] Next, the solution is concentrated and dried by an evaporator, vacuum dried at 80 to 130°C, and then fired in a nitrogen atmosphere at 500 to 900°C for 5 to 120 minutes. In this firing, the material source of the water-resistant layer coats the electrode material to become the water-resistant layer. In the coating process, the electrode material obtained in the crystallization process is added to the solution, and the structure of the electrode material is changed by moisture. However, by carrying out this firing, the electrode material with the changed structure is crystallized again. As a result, a water-resistant layer is formed on the electrode material obtained in the crystallization process. The above is the processing of the coating process.
[0046] [Effects] As described above, the electrode material of the present embodiment includes lithium vanadium phosphate bonded to a conductive carbon material, and the lithium vanadium phosphate has a water-resistant layer. By having the lithium vanadium phosphate have a water-resistant layer in this way, it is possible to suppress structural changes caused by moisture. In addition, when the water-resistant layer has a crystal structure of a phosphate-based compound, it has a high affinity with lithium vanadium phosphate, and it is possible to further suppress changes in the crystal structure caused by moisture.
[0047] When the water-resistant layer contains an aluminum phosphate compound or a titanium phosphate compound, the influence of moisture is suppressed, and the elution of vanadium into moisture is more effectively suppressed. When the water-resistant layer is formed so that the content of the compound is 5 to 25 wt % relative to lithium vanadium phosphate, there is no risk of a decrease in electrode capacity or an increase in resistance. EXAMPLES
[0048] The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0049] Example 1 In this Example 1, an electrode material made of a composite of lithium vanadium phosphate and carbon nanotubes (hereinafter sometimes referred to as CNTs) and having a water-resistant layer containing AlPO4 was produced by the manufacturing procedure shown below.
[0050] The material sources of lithium vanadium phosphate are ammonium metavanadate (NH4VO3), lithium acetate (CH3COOLi), and phosphoric acid (H3PO4). The average fiber diameter of the CNT is 15 to 30 nm. The weight ratio of each material source of lithium vanadium phosphate to CNT is 70:30.
[0051] First, a mixed solution was prepared by adding 1.58 g of H3PO4 and 0.8 g of CNT to distilled water. This mixed solution was subjected to UC treatment using the above reactor in an environment of 80°C. For the UC treatment, the inner cylinder was rotated at a rotation speed of 50 m / s, and a centrifugal force of 66000 N (kgms-2) was applied to the mixed solution for 5 minutes.
[0052] To the resulting mixture, 1.08g of NH4VO3, 1.77g of citric acid, 0.93g of CH3COOLi, and 20g of distilled water were added. Furthermore, 2.29g of ethylene glycol and 22g of distilled water were added. As a result, a metal complex was formed between the vanadium ions and citric acid, and the citric acid further formed a polymer by an ester reaction with ethylene glycol. The polymer formed by this polymerization reaction penetrates between the metal complexes, dispersing them and maintaining their dispersed state. The mixture was subjected to UC treatment under the same conditions as above.
[0053] The mixture was then concentrated and dried using an evaporator, vacuum dried at 80°C, and pre-baked at 300°C for 5 hours. It was then baked in a nitrogen atmosphere at 800°C for 60 minutes. Through these crystallization steps, an electrode material in which lithium vanadium phosphate was bonded to the surface of the CNT was obtained.
[0054] Next, the metal source (Al(NO3)3) for the water-resistant layer and the phosphate source ((NH4)2HPO4) for the water-resistant layer, dissolved in distilled water, were added to the obtained electrode material. 1.19g of 20wt% Al(NO3)3 aqueous solution and 0.08g of (NH4)2HPO4 were added to 2.2g of electrode material. The above mixture was subjected to UC treatment under the same conditions as above.
[0055] The mixture was then concentrated and dried using an evaporator, vacuum dried at 80°C, and then baked in a nitrogen atmosphere at 800°C for 30 minutes. Through the above coating process, lithium vanadium phosphate was bonded to the surface of the CNTs, yielding an electrode material in which a water-resistant layer containing 5 wt% AlPO4 was formed relative to the electrode material.
[0056] Example 2 In this Example 2, an electrode material made of a composite of lithium vanadium phosphate and CNT and having a water-resistant layer containing LiTi2(PO4)3 was produced by the following manufacturing procedure. The crystallization process was the same as in Example 1.
[0057] In the coating process, the metal source for the water-resistant layer (Ti(O) dissolved in ethanol) was added to the obtained electrode material. n The electrode material was added with 0.45 g of Ti(O n 0.04g of Bu) and 10g of ethanol were added. Furthermore, 6g of distilled water, 0.02g of NH4H2PO4, 0.004g of CH3COOLi, and 0.01g of citric acid were added. The above mixture was subjected to UC treatment under the same conditions as above.
[0058] The mixture was then concentrated and dried using an evaporator, vacuum dried at 80°C, and then re-fired in a nitrogen atmosphere at 800°C for 30 minutes. Through the above coating process, lithium vanadium phosphate was bonded to the surface of the CNTs, yielding an electrode material in which a water-resistant layer containing 5 wt% LiTi2(PO4)3 was formed.
[0059] Example 3 The manufacturing method of the electrode material of Example 3 is the same as that of Example 2. However, the electrode material was prepared by adding 0.45 g of Ti(O n Bu)4, 0.21 g, NH4H2PO4, 0.10 g, CH3COOLi, 0.02 g, and 0.06 g of citric acid were added to form a water-resistant layer containing 25 wt% LiTi2(PO4)3 with respect to the electrode material.
[0060] Comparative Example 1 The manufacturing method of the electrode material of Comparative Example 1 was the same as the crystallization step of the above-mentioned Example 1. However, the electrode material of Comparative Example 1 was not subjected to the coating step, and no water-resistant layer was formed.
[0061] Comparative Example 2 The electrode material of Comparative Example 1 was left for six days in a low humidity environment at room temperature of 20 to 25° C. and humidity of about 0%, to prepare an electrode material of Comparative Example 2.
[0062] Comparative Example 3 The electrode material of Comparative Example 1 was left in a high humidity environment at room temperature of 20 to 25° C. and humidity of about 80% for 6 days to obtain an electrode material of Comparative Example 3.
[0063] <Water resistance of lithium vanadium phosphate> The water resistance of lithium vanadium phosphate not having a water-resistant layer was examined using the above Comparative Examples 1 to 3. That is, the crystal structure of Comparative Example 1, which is an electrode material immediately after production, Comparative Example 2, which is an electrode material after being left at low humidity, and Comparative Example 3, which is an electrode material after being left at high temperature, was analyzed by XRD (X-ray powder diffraction method). The results are shown in Figure 3.
[0064] As is clear from Fig. 3, in the diffraction pattern of Comparative Example 1 immediately after production, peaks characteristic of lithium vanadium phosphate were confirmed at around 2θ = 21 degrees, 24 degrees, and 29 degrees. Furthermore, in Comparative Example 2 after being left at low humidity, peaks similar to those of Comparative Example 1 were confirmed. From this result, it was confirmed that the crystal structure of the electrode material in which lithium vanadium phosphate and a conductive carbon material are combined does not change even if it is left in a low humidity environment with a humidity of around 0%.
[0065] On the other hand, in Comparative Example 3 after being left at high humidity, the characteristic peaks of lithium vanadium phosphate disappeared. In addition, as shown by the * and diamond marks in the figure, peaks that were not confirmed in Comparative Example 1 were detected. Of these, the * peaks were presumed to be peaks derived from Li3PO4, but the diamond peak was unknown. From this result, it was confirmed that the crystal structure of Comparative Example 3 had changed and decomposed due to being left at high humidity. In other words, it was revealed that lithium vanadium phosphate is easily affected by moisture in the air and has low stability.
[0066] <Observation of crystal structure> For Examples 1 to 3 and Comparative Example 1, HRTEM images were taken by focusing on the crystals of the electrode material using a high-resolution transmission electron microscope. FIG. 4 shows HRTEM images of Comparative Example 1 and Example 1. FIGS. 4(a) and (b) are HRTEM images taken at a magnification of 20,000 times. At this magnification, the overall crystal structure of Comparative Example 1 and Example 1 was confirmed, and it was found that both were electrode materials in which lithium vanadium phosphate was bonded to CNTs.
[0067] Figures 4(c) and (d) are HRTEM images taken at a magnification of 300,000 times. The HRTEM image of Comparative Example 1 in Figure 4(c) is a particle image of lithium vanadium phosphate, but no layer formation on the particle surface can be confirmed. On the other hand, in the HRTEM image of Example 1 in Figure 4(d), it was confirmed that a layer was formed on the surface of the lithium vanadium phosphate particle, as partially indicated by the arrow in the figure.
[0068] FIG. 5 shows HRTEM images of Examples 2 and 3. FIGS. 5(a) and (b) are HRTEM images at a magnification of 150,000 times, and FIGS. 5(c) and (d) are HRTEM images at a magnification of 300,000 times. From FIGS. 5(a) and (c), it was confirmed that a granular layer was formed on the surface of the lithium vanadium phosphate particles of Example 2. Also, from FIGS. 5(b) and (d), it was confirmed that a uniform layer was formed on the surface of the lithium vanadium phosphate particles of Example 3.
[0069] <Method for evaluating water resistance of lithium vanadium phosphate> A test method for evaluating the water resistance of lithium vanadium phosphate was examined and the test was carried out as follows. The test method was as follows: 0.1 g of electrode material immediately after production was added to 1 cc of distilled water and stirred for 10 minutes by ultrasonic treatment. After that, the mixture was left at 60 degrees for 47 hours using a heating device. The mixture after the heat treatment was filtered, and XRD analysis was performed on the obtained powder. ICP emission spectroscopy was performed on the filtrate to measure the amount of vanadium eluted. XRD analysis was also performed on the electrode material before the test and the results were compared with those after the test.
[0070] FIG. 6 shows the results of XRD analysis performed before and after the test on the electrode material of Comparative Example 1. A characteristic peak of lithium vanadium phosphate was confirmed in the electrode material before the test. However, in the electrode material after the test, the characteristic peak disappeared, and only the peak derived from CNT was confirmed. From this result, it was confirmed that the electrode material of Li3V2(PO4)3 / CNT such as Comparative Example 1 is vulnerable to moisture, and when this test was performed, almost all of the lithium vanadium phosphate was dissolved in the filtrate.
[0071] Next, FIG. 7 shows the results of XRD analysis performed before and after the test on the electrode material of Example 1. For the electrode material of Example 1, there was no significant change in the peak value of the diffraction pattern before and after the test. From this result, it was confirmed that the electrode material of Li3V2(PO4)3 / CNT coated with a water-resistant layer containing AlPO4 as in Example 1 is not easily affected by moisture, and no significant change occurs in the crystal structure even when this test is performed, and dissolution of lithium vanadium phosphate into the filtrate is suppressed.
[0072] Next, the results of ICP emission spectroscopic analysis performed on the electrode materials of Comparative Example 1 and Example 1 before and after the test are shown in Table 1. [Table 1]
[0073] From Table 1, in Comparative Example 1, which does not have a water-resistant layer, 86.6% of the vanadium added was dissolved into the filtrate. On the other hand, in Example 1, which has a water-resistant layer containing AlPO4, 31.3% of the vanadium added was dissolved into the filtrate. From the above results, it was revealed that the electrode material provided with a water-resistant layer containing AlPO4 has the effect of moisture suppressed by the water-resistant layer, and the dissolution of vanadium into moisture is suppressed.
[0074] <Consideration of the amount of addition> The above-mentioned tests to evaluate the water resistance were also conducted for Examples 2 and 3. FIG. 8(a) shows the results of XRD analysis performed before and after the test for the electrode material of Example 2. FIG. 8(b) shows the results of XRD analysis performed before and after the test for the electrode material of Example 3. For the electrode materials of Examples 2 and 3, the peak values of the diffraction patterns of the electrode materials before and after the test did not change significantly. From these results, it was confirmed that the electrode material of Li3V2(PO4)3 / CNT coated with a water-resistant layer containing LiTi2(PO4)3 as in Examples 2 and 3 is not easily affected by moisture, and the crystal structure does not change significantly even when this test is conducted, and the dissolution of lithium vanadium phosphate into the filtrate is suppressed.
[0075] Next, the results of ICP emission spectroscopic analysis performed on the electrode materials of Examples 2 and 3 before and after the test are shown in Table 2. [Table 2]
[0076] From Table 2, in Example 2 having a water-resistant layer containing 5 wt% LiTi2(PO4)3 relative to lithium vanadium phosphate, 37.7% of the vanadium added was dissolved in the filtrate, which was equivalent to the result in Example 1 having a water-resistant layer containing 5 wt% AlPO4 relative to lithium vanadium phosphate.
[0077] In Example 3, which has a water-resistant layer containing 25 wt% LiTi2(PO4)3 relative to lithium vanadium phosphate, 23.3% of the vanadium added was dissolved into the filtrate. From the above, it was found that by increasing the ratio of the water-resistant layer to the lithium vanadium phosphate, a more uniform coating of the water-resistant layer is possible, the effect of moisture is further suppressed, and the dissolution of vanadium into moisture can be suppressed.
[0078] <Cell capacity retention rate> The electrode materials of Examples 1, 2, and 3, and Comparative Example 1 were made into electrodes using PVDF, and the counter electrode was made of L4T5O 12 A full cell was prepared using 1M LiPF6 / EC+DEC 1:1 (in volume) as the cell and electrolyte, and the capacity retention rate was evaluated. As a result, the capacity retention rate of Comparative Example 1, which does not have a water-resistant layer, was 77%, the capacity retention rate of Example 1, which has a water-resistant layer containing 5 wt% AlPO4 relative to lithium vanadium phosphate, was 89%, and the capacity retention rate of Example 2, which has a water-resistant layer containing 5 wt% LiTi2(PO4)3 relative to lithium vanadium phosphate, was 87%. In addition, the capacity retention rate of Example 3, which has a water-resistant layer containing 25 wt% LiTi2(PO4)3 relative to lithium vanadium phosphate, was 91%.
[0079] From these results, it was found that even when a water-resistant layer containing AlPO4 or LiTi2(PO4)3 was formed, the charge / discharge characteristics were equivalent to those of an electrode material that did not have a water-resistant layer. It was also confirmed that the capacity retention rate did not change depending on the content of LiTi2(PO4)3. In other words, it was confirmed that the presence of a water-resistant layer containing AlPO4 or LiTi2(PO4)3 did not cause deterioration in the charge / discharge characteristics.
Claims
1. comprising lithium vanadium phosphate bound to a conductive carbon material; The lithium vanadium phosphate has a water-resistant layer, the water-resistant layer has a crystal structure of a phosphate-based compound, The water-resistant layer having a crystal structure of the phosphate-based compound is an aluminum phosphate compound, a titanium phosphate compound, or X α M β (P.O. 4 ) γ where X is any one of Li, Na, K, and Ca, and M is any one of Al, Mn, Co, Fe, Mg, Ni, Ti, Zn, Cr, Ni, Cu, Zr, and Nb. The water-resistant layer is a water-resistant layer formed before forming an electrode.
2. The aluminum phosphate compound is AlPO 4 The electrode material according to claim 1 .
3. The titanium phosphate compound is LiTi 2 (P.O. 4 ) 3 The electrode material according to claim 1 .
4. 4. The electrode material according to claim 1, wherein the water-resistant layer is formed so as to have a content of 5 to 25 wt % relative to lithium vanadium phosphate.
5. a crystallization step of combining the conductive carbon material with lithium vanadium phosphate; A coating step of forming a water-resistant layer on the electrode material obtained by the crystallization step, The coating step includes a mixing step of mixing a material source of a water-resistant layer in a solution with the electrode material obtained by the crystallization step; A baking step of baking the solution obtained in the mixing step, The water-resistant layer has a crystal structure of a phosphate-based compound.
6. The water-resistant layer having a crystal structure of the phosphate-based compound is an aluminum phosphate compound, a titanium phosphate compound, or X α M β (P.O. 4 ) γ 6. The method for producing an electrode material according to claim 5, wherein X is any one of Li, Na, K, and Ca, and M is any one of Al, Mn, Co, Fe, Mg, Ni, Ti, Zn, Cr, Ni, Cu, Zr, and Nb.
Citation Information
Patent Citations
Manufacturing method of electrode material, positive electrode material, and battery
JP2008052970A
Process of producing vanadium lithium phosphate carbon composite
JP2012036050A
Positive electrode active material and method for producing the same
JP2012151037A
Electrode material for power storage device and manufacturing method thereof
JP2014229830A
Lithium ion secondary battery
JP2016001595A